Perceptions of Cannabis Use: A Qualitative Descriptive Study of Rheumatology Patients - Joanne Olson; Hailie Brophy; Tarek Turk; Allyson Jones; Shelby. S. Yamamoto; Elaine Yacyshyn; Cheryl A. Sadowski; Pauline Paul (SAGE Publishing, 2023)
Introduction/Objectives: Some rheumatology patients use or contemplate using cannabis, however, may not be transparent about use with their providers. The objective of this qualitative descriptive study was to describe beliefs, perceptions, and learning needs of adults with rheumatic conditions regarding the use of cannabis products. Methods: Purposive sampling was conducted through a rheumatology clinic and sought participants who were using or thinking about using cannabis. Two online focus groups based on cannabis use patterns (non-users and users) were conducted separately. Interviews were audio recorded and transcribed. Three research team members read the transcripts independently to identify initial codes and themes. Data saturation was reached with the interviews. Results: We recruited 12 participants between 52 and 85 years old. The first theme was pain and desperation. Stigma was the second theme with a perception of physician opposition to cannabis, and the reluctance of many participants to discuss cannabis use with physicians. The final theme was a need for information and a general lack of trustworthy and credible sources. Users were willing to try cannabis even if they still had questions. Conclusion: Rheumatology patients are open to using cannabis due to the burden and suffering associated with pain. They remain silent on the topic, however, because of stigma and lack of engagement from health care professionals, particularly physicians. Patients voiced a strong need for information regarding cannabis and want healthcare providers to initiate discussion. These findings are clinically relevant to the management of rheumatic conditions and the promotion of therapeutic relationships.